Evaluation of Health and Wellness Centers in Nagpur District of Maharashtra, Central India - Priti N. Tiwari; Sagar M. Pandey; Hitesh C. Tayade; Arvind S. Kushwaha; Sushma S. Thakre; Subhash B. Thakre (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Background: The health and wellness centers (HWCs) strengthen and deliver comprehensive primary health care services for the entire population covered under them. HWCs provide an expanded range of services. Establishing HWCs involves a paradigm shift in many dimensions, including innovations in human resources, provision of medication for chronic conditions, financial reforms, and use of digital and information technology. The present study was undertaken to evaluate the health and wellness centers under various domains. Methods: A cross-sectional study was carried out as a part of an evaluation. A total of eight health and wellness centers subcenter (HWCs-SC) were selected from the Nagpur district by a convenient sampling technique. The availability of human resources, equipment, laboratory services, and drugs was assessed using the Indian Public Health Standards (IPHS) Facility Assessment Checklist. Data were entered in a Microsoft Office Excel 2013 and analyzed using numbers and percentages. Results: All eight HWCs were functioning in government buildings. Half of the HWCs had electricity and functional power backup. Community Health Officer (CHO) was appointed at seven out of eight HWCs. At least one multipurpose worker (MPW) was available at 5 (62.50%) of HWCs. Conclusion: HWCs were found to be deficit in every domain. Poor infrastructure, lack of water and electricity, understaffing, inadequate essential and emergency drug supply, and insufficient laboratory services were common issues. A higher level of patients and community satisfaction was observed. None of the HWC-SC was able to meet the specifications of IPHS norms in reference to all the study domains. Recommendations: This study highlights the operational gaps in implementation of comprehensive primary health care through Ayushman Bharat health and wellness centers (HWCs) in Maharashtra. It presents crucial information for program managers, policymakers, and primary care practitioners, to understand and address local implementation problems to streamline the program. Addressing these gaps would help achieve the outcomes of improved population coverage, reduced out-of-pocket expenditure, decongestion of higher facilities, and ultimately universal health coverage.